2012
DOI: 10.4103/0976-9668.95961
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial lipemia in pre- and postmenopausal women

Abstract: Background and Objective:The increased risk for coronary artery disease observed in postmenopausal (PoW) women is partly explained by a more atherogenic lipoprotein profile. Moreover, natural menopause has been associated with an altered postprandial lipid profile. This study was designed to test the hypothesis that young premenopausal (PrW) and PoW may be independently associated with postprandial lipemia and indirectly associated with atherosclerosis.Patients and Methods:A total of 46 healthy PrW and 44 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…In addition to GLU, other parameters including TC, HDL, and LDL also did not appear to present significant differences between groups. Previous studies of acute resistance exercise and PPL have not detected any difference in fasting TC (Burns et al 2005;Zafeiridis et al 2007), HDL (Shannon et al 2005), and LDL (Zaman et al 2012) concentrations between low-and high-volume resistance exercise groups and CG. Moreover, the bulk of evidence derived from the present research and other studies (Burns et al 2005;Shannon et al 2005) indicates that resistance exercise does not influence fasting TC, HDL, and LDL concentrations.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In addition to GLU, other parameters including TC, HDL, and LDL also did not appear to present significant differences between groups. Previous studies of acute resistance exercise and PPL have not detected any difference in fasting TC (Burns et al 2005;Zafeiridis et al 2007), HDL (Shannon et al 2005), and LDL (Zaman et al 2012) concentrations between low-and high-volume resistance exercise groups and CG. Moreover, the bulk of evidence derived from the present research and other studies (Burns et al 2005;Shannon et al 2005) indicates that resistance exercise does not influence fasting TC, HDL, and LDL concentrations.…”
Section: Discussionmentioning
confidence: 60%
“…A progressive reduction in muscle mass (sarcopenia) due to the aging process (Chapman et al 2002;Zaman et al 2012) is usually associated with functional impairment and functional disability and is a direct cause of reduced muscle strength (Correa et al 2012;Tzankoff and Norris 1977). Furthermore, physical inactivity and loss of muscle mass with aging lead to loss of muscle strength and endurance (Kanaya et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the increased serum triglycerides concentrations and associated PPL at the onset of menopause may increase the risk of coronary heart disease in this group when compared to men (Zaman, Rahman, & Rahman, 2012). Therefore, any intervention that reduces coronary heart disease risk is particularly relevant for this group.…”
Section: Discussionmentioning
confidence: 95%
“…Secondly, the effects of cyclic hormone concentrations on lipid metabolism may confound the study of premenopausal women (Binzen et al, 2001). Recently, Zaman et al (2012) preformed a protocol of OFTT, without performing any type of exercise, comparing premenopausal with postmenopausal women. The triglycerides serum was significantly higher in the postmenopausal participants, and the authors concluded that the PPL response indicated 1.16 ± 0.55 P = 0.59, P = 0.23, P = 0.81…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial function deteriorates in the same proportion as lipemia increases, as in an acute response to systemic changes, whether chronic or postprandial. 3 The phenomenon is associated with increased secretion of pro-inflammatory cytokines, expression of adhesion molecules (ICAM, VCAM-1) and prooxidative activity. The endothelial damage observed during this process promotes recruitment of injury-responsive cells by stimulating infiltration of monocytes to the subendothelial space, which d ifferen tiate into m acrophages (foam cells), which are well-known to exhibit the ability to accumulate large amounts of lipids originating from cytoplasm-generating products that induce tissue damage and reactive oxygen and nitrogen species.…”
Section: ■ Introductionmentioning
confidence: 99%